ANALYSIS OF THE VOLATILE COMPONENTS OF THE AERIAL PARTS OF HYPERICUM LARICIFOLIUM JUSS. FROM NORTHERN PERU - Collantes Díaz, Ingrit E. (2024)
The aerial parts of the ephemeral shrub Hypericum laricifolium were collected in March 2021 in Pataz (La Libertad). The oil essential was obtained by hydrodistillation and was analyzed by gas chromatography coupled to a mass spectrometer. 97 compounds of the essential oil were identified, including oxygenated monoterpenes, sesquiterpenes hydrocarbons, sesquiterpenes oxygenated among others, of which the major components were the 2-methyloctane (5,32%), n-nonane (10,2%), α-pinene (9,34%), Z-β-ocimene (13,33%), E-β-ocimene (3,15%), Z-caryophyllene (3,24%), caryophyllene oxide (8,71%) and citronella pentanoate (4,66%).